2002
DOI: 10.1002/j.2333-8504.2002.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Patterns of Gender Differences on Mathematics Admissions Tests

Abstract: A two-part study was conducted to determine whether theoretical work examining gender differences in cognitive processing can be applied to quantitative items on the Graduate Record Examination (GRE ® ) to minimize gender differences in performance. In Part I, the magnitude of gender differences in performance on specific test items was predicted using a coding scheme. In Part II, a new test was created by using the coding scheme developed in Part I to clone items that elicited few gender-based performance dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 9 publications
0
37
0
2
Order By: Relevance
“…However, in contrast to Gallagher et al (2000Gallagher et al ( , 2002, Harris and Carlton (1993) found that girls actually excel at abstract math items and that boys excel at applied items. Gallagher et al (2002) applied a similar approach in their analysis of the GRE-Q. They found that it is possible to manipulate the performance of males and females by changing the mix of question types and criticized the lack of a theory-driven basis for the SAT-M and GRE-Q tests (see pp.…”
Section: Aptitude Testsmentioning
confidence: 66%
“…However, in contrast to Gallagher et al (2000Gallagher et al ( , 2002, Harris and Carlton (1993) found that girls actually excel at abstract math items and that boys excel at applied items. Gallagher et al (2002) applied a similar approach in their analysis of the GRE-Q. They found that it is possible to manipulate the performance of males and females by changing the mix of question types and criticized the lack of a theory-driven basis for the SAT-M and GRE-Q tests (see pp.…”
Section: Aptitude Testsmentioning
confidence: 66%
“…The largest male advantage is found in math tasks that involve visuospatial abilities, with gender differences of 0.9 to 1.0 standard deviations. Casey et al (1995) show that, when questions which rely on visuospatial abilities are statistically removed from the math SAT, the sex difference in scores disappears; Gallagher and DeLisi (1994) and Gallagher et al (2002) find a similar pattern for the Quantitative Reasoning section of the Graduate Record Examination (GRE). 24 For example, in 2 nd grade, we gave children an unmarked number line with the values 0 and 50 on each end, and asked them to place five randomly generated numbers between 1 and 49 on this line.…”
Section: B Differences In the Distribution Of Test Scoresmentioning
confidence: 96%
“…The social significance of the documented gender disparities in achievement remains unclear, as these disparities are shown to have limited power to explain those in STEM participation (Xie & Shauman 2003; Weinberger 2005). Commonly used standardized tests may be poor instruments for measuring gender differences in STEM aptitude (Gallagher et al 2002; Halpern 2002), since research suggests that item content may bias the scores (Chipman 2005; Spelke 2005), and that they have limited power to predict actual task performance and STEM achievement for girls (Schmidt 2011). Recent research also highlights the need to estimate the potential influence of math or science achievement in relation to achievement in other domains (Lubinski & Benbow 2006; Riegle-Crumb et al 2012; Wang et al 2013).…”
Section: Gender and Stem Educationmentioning
confidence: 99%